The Use of Artificial Intelligence in Human Resources Processes as Part of Sustainable Development: Political and Organizational Aspects - Bieliaieva, Nataliia; Tymoshenko, Maryna; Nalyvaiko, Nataliia; Khmurova, Viktoriia; Sychova, Nina (Journal of the University of Zulia, 2023)
The article characterizes and defines the directions of artificial intelligence technology use in modern organizations and discusses those categories that will remain promising in the future. It highlights the main advantages and risks that currently exist with respect to the use of artificial intelligence and its development in Human Resources processes (HR processes). It was concluded that the main areas of use of artificial intelligence technology in modern organizations and categories that will continue to be promising in the future are defined: automation and optimization of processes; generating insights for decision making. It was emphasized that, in order to prevent the emergence of threats to humanity, in the process of developing artificial intelligence, specialists must establish certain restrictions and its developers must prioritize the issue of protection of user data and ensure control of its use.